Mengelola Uang Usaha dengan Cerdas agar Bisnis Tetap Cuan dan Tumbuh - Salza Adzri Arismutia (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2026)
Many Micro, Small, and Medium Enterprises (MSMEs) still face fundamental problems in business financial management, including low financial literacy, lack of discipline in recording transactions, the absence of separation between personal and business finances, and weak budgeting practices. These issues result in uncontrolled cash flow, difficulties in accurately measuring profits, increased risk of financial loss, and obstacles to sustainable business stability and growth. This community service activity aims to improve the understanding, capabilities, and skills of business actors in managing business finances intelligently, effectively, and systematically so that businesses can remain profitable, survive economic challenges, and grow sustainably amid increasingly complex business competition. The method used in this service program was a descriptive educational approach through counseling, training, and mentoring for MSME actors, employing qualitative analysis techniques on the implementation of financial management strategies, including routine financial recording, cash flow management, budgeting, expenditure evaluation, and the utilization of digital financial technology as a supporting tool for efficiency and accuracy in business management. The results of the service activity indicate that the implementation of proper financial management strategies can improve operational efficiency, strengthen financial control, support more rational business decision-making, reduce the risk of losses, and encourage increased profitability and sustainable business growth. Therefore, intelligent business financial management is an essential factor in maintaining long-term business stability and success.